Pengaruh Kepemimpinan Transformasional dan Keterlibatan Kerja terhadap Organizational Citizenship Behavior (OCB) melalui Mediator Kepuasan Kerja - Naimah, Muflikhatun; tentama, Fatwa tentama; Diah Sari, Erita Yuliasesti (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2022)
Teachers of extraordinary school (SLB) have a heavier and more varied workload than general teachers. In addition of carrying out administrative works, extraordinary school teachers face challenges in educating children with special needs who also require special handling. Organizational Citizenship Behavior (OCB) is required to overcome this situation. This study aims to test the model of transformational leadership effect and job involvement on OCB with job satisfaction as a mediator of SLB teachers. Participants in this study was 88 SLB teachers from State Extraordinary School "X", State Extraordinary School "Y", and State Extraordinary School “Z”. The data collection method used the transformational leadership scale, job involvement, job satisfaction, and OCB. The data analysis technique used the Structural Equation Model (SEM) through the Partial Least Square (PLS) program. The results of the study showed that the effect of transformational leadership and job involvement on OCB with job satisfaction mediator is in accordance with the empirical data. Partially, transformational leadership has a positive and significant effect on job satisfaction, transformational leadership has a positive and significant effect on OCB, job involvement has a positive and significant effect on job satisfaction, job involvement has a positive and significant effect on OCB, job satisfaction has a positive and significant effect on OCB. Job satisfaction can be a good mediator between transformational leadership on OCB and job involvement on OCB. The OCB model has been tested and can be applied as an effort to improve OCB for SLB teachers.